Locus-wide studies into the transcriptional regulation of Runx1 in developmental hematopoiesis - Jarratt, A (2012)
Developmental hematopoiesis sees the generation of the first blood cells and definitive blood during embryonic development. The founding cell of definitive hematopoiesis, the hematopoietic stem cell (HSC), gives rise to all adult blood lineages throughout the life span of an organism. It is expected that future ex-vivo manipulation of HSCs for therapeutic uses will benefit from a thorough understanding of the mechanisms, both cellular and genetic, that give rise to HSCs. One of the most critical regulators of HSC emergence in the embryo is the transcription factor (TF) Runx1. One aim of our lab is to decipher what controls the cis-regulation of Runx1 to understand better how it exerts its function in the emergence of HSCs. In this thesis, chromatin assays were used to identify putative enhancers within the 1.3 Mb Runx1 syntenic region. Seven novel enhancers were identified that mediate reporter gene expression in discrete patterns of Runx1-specific hematopoietic expression in transient transgenic embryos. Characterization of the cells marked by one of these enhancers, the +110 enhancer in a transgenic mouse line, showed that it is active in clonogenic progenitors at E11.5, but, interestingly, not HSCs. Finally, chromosome conformation capture (3C) assays showed physical interactions between the Runx1 P1 and P2 promoters and between the Runx1 P1 and P2 promoters and putative regulatory elements in the 1.3 Mb syntenic region. Together, these data increase our understanding of the complexity of Runx1 cis-regulation during development and provide a starting point for characterizing what upstream trans-acting factors converge on Runx1 to specify blood.